PERFORMING LIFESTYLE POLITICS: EXPLORING THE SLOW FASHION COMMUNITY ON INSTAGRAM - Ataman, Jimil (AoIR Selected Papers of Internet Research, 2021)
This paper explores the unique discursive register being created by slow fashion practitioners on Instagram. The slow fashion movement includes people, practices, ideas, and things from all over the world and online - all of which are broadly connected through a shared effort to resist and transform the waste-driven, profit-seeking, inequitable and unjust system(s) which produce and sustain contemporary fashion. In this paper I analyze three key performable roles which slow fashion practitioners are embodying on Instagram as a way to perform the politics of the movement: (1) Outfit of the Day Posts (OOTD), (2) wardrobe tracking, and (3) knowledge-sharing posts. In discussing each of these instances of popular slow fashion performances, I will examine what each example is “saying” and “doing” within the slow fashion community and analyze how these performances are positioned within the community’s broader ethical and political goals. By exploring the kinds of performances most commonly posted on Instagram I draw attention to the ways slow fashion practitioners’ performances are both assembling individual practitioner identity (or ‘self’) to the wider slow fashion community as well as producing a wider register of lifestyle politics in the slow fashion movement.